Analisa Deteksi Orisinalitas Citra Digital Menerapkan Metode Tiger - Sari, Puspa (TIN: Terapan Informatika Nusantara, 2021)
The development of digital images is now very fast, it makes images easy to create and edit. With this development, many people abuse it by manipulating images. Image processing in digital images can be created or edited easily, without even leaving visual clues to its use. The ease in creating and changing an image can damage the credibility of the authenticity of the image in various aspects, thus making it prone to be used for criminal acts because image changes in digital images can change the information conveyed to be different. This is the basis of this research to detect the authenticity of an image. The method used in detecting image originality is the tiger method, in accordance with the main function of the hashing function, which functions to retrieve a marker from an image which will later be used as a reference to check whether an image is real or fake. The index calculation will be converted into decimal form so that the type of index value is known and the calculation is carried out on the file which will be corrected using matlab.